1996
DOI: 10.1108/01443579610119054
|View full text |Cite
|
Sign up to set email alerts
|

Do companies need to measure their production flexibility?

Abstract: Although there is a vast body of literature that attempts to define production flexibility, managers are still unable to measure the flexibility they require. However, managers currently are investing in flexible manufacturing systems (FMSs) and planning their manufacturing strategies despite this. Discusses the flexibility and economic viability of FMSs, and concludes that managers do not need to measure the flexibility of an FMS in order to select the correct technical specification. Describes the factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…2, if we have an accurate model then for decision making no flexibility measure is required per se. This same idea is reiterated by Primrose and Verter (1996) who indicate that managers need not measure the flexibility of an FMS in order to select the correct technical specification, but should focus on the benefits to be achieved from an FMS and on the design that optimizes its benefits. Some flexibility to cope with change and disturbance can be justified, but only to the extent needed to optimize overall performance.…”
Section: Flexibility and Effectiveness Of The Production Systemmentioning
confidence: 90%
“…2, if we have an accurate model then for decision making no flexibility measure is required per se. This same idea is reiterated by Primrose and Verter (1996) who indicate that managers need not measure the flexibility of an FMS in order to select the correct technical specification, but should focus on the benefits to be achieved from an FMS and on the design that optimizes its benefits. Some flexibility to cope with change and disturbance can be justified, but only to the extent needed to optimize overall performance.…”
Section: Flexibility and Effectiveness Of The Production Systemmentioning
confidence: 90%
“…In addition, there is some indication that faulty or inadequate investment justification practices can result in firms not recognising or considering some benefits which the AMT may indeed be capable of bestowing (Primrose, 1991;Small and Chen, 1995;Burcher and Lee, 2000;Lefley et al, 2004;Teng and Seetharamam, 2004;Dangayach and Deshmukh, 2005;Salaheldin, 2007). As an example, Primrose (1991) indicated that if the strategic benefits of an AMT are not quantified in the appraisal, they will appear as unexplained variances not attributable to the project in the accounting report.…”
Section: Introductionmentioning
confidence: 93%
“…Pre-planning stage Linking business and manufacturing strategies Anderson, Cleveland and Schroeder, 1989;Carlson, Gardner and Ruth, 1989;Cleland and Bursic, 1992;Udoka and Nazemetz, 1990;Zahra and Covin, 1993 Coordinating marketing and manufacturing strategies Blois, 1986Blois, , 1991Gupta, 1988;Haskins and Petitt, 1988;Hayes and Wheelwright, 1985;Hershfield, 1992;Hill, 1985;Vrakking, 1989 Developing an automation/technology strategies Swamidass and Waller, 1991;Blois, 1986;Hershfield, 1992;Dornan, 1987 Monitoring advanced manufacturing technologies Attaran, 1992;Chen and Small, 1994;Chung, 1991;Swamidass, 1987 Planning for AMT Top-management involvement Beatty, 1990;Boer, Hill and Krabbendam, 1990;Hershfield, 1992;Klein, Conn and Sorra, 2001;Meredith, 1988;Rubenowitz, Olsson and Steen, 1990;Udo and Ehie, 1996 Establishing multi-disciplinary planning teams Beatty, 1990;Doll and Vonderembse, 1987;Dornan, 1987;Gerwin and Kolodny, 1992;Hershfield, 1992;Udo and Ehie, 1996 Matching capabilities of AMT to the benefits expected by the firm Primrose, 1991;Teczlaff, 1990;Udoka and Nazemetz, 1990;Udo, Ehie and Olorunniwo, 1995 Ensuring compatibility of AMT with existing systems …”
Section: Critical Activity Sourcementioning
confidence: 99%
“…Capacity to handle new product A particular manufacturing system will be more flexible if it is capable of handling the more number of new and unexpected products. Primrose (1996) has proposed FMS results in introduction of new products. 3.…”
Section: Literature Reviewmentioning
confidence: 99%